Observed Changes in Fine Motor Coordination in Elementary School Students ThroughDuring Bola Serimbang: A Traditional Indonesian Ball-and-Stones Game - Myrza Akbari; Johaidah Mistar; Rahmati Rahmati; Myrna Lestari; Razali Razali; M. Adam Mappaompo; Zikrur Rahmat (Sakura Digital Nusantara, 2026)
Background: Fine motor coordination supports children's early writing, self-care, and precise object manipulation, yet it may receive limited structured practice in elementary physical education. This study described changes in fine motor coordination during Bola Serimbang, a traditional Indonesian ball-and-stones game. Methods: Classroom action research following the Kemmis and McTaggart model was implemented over three cycles and nine meetings with 63 first-grade students (34 girls and 29 boys) at SD Negeri 2 Kebun Lama, Langsa City. Ten progressive game stages emphasized grasping, controlled release, tossing, catching, and stone manipulation. Fine motor performance was assessed using a four-indicator observation rubric. The practical success criterion was at least 70% of students reaching Developing as Expected (BSH) or Very Well Developed (BSB). Results: The cycle summary tables indicated that the proportion reaching BSH or BSB increased from 47.62% (30/63) at the end of Cycle I to 57.14% (36/63) in Cycle II and 85.71% (54/63) in Cycle III. At the end of Cycle III, 25.40% reached BSH and 60.32% reached BSB, while no students remained in the Undeveloped category. Conclusions: Within this single-group classroom action research, higher end-of-cycle category distributions were observed during progressively changing tasks. Bola Serimbang may offer a low-cost, culturally relevant activity for elementary physical education, but source-record verification and controlled, blinded studies are needed before causal effectiveness can be established.